2007
DOI: 10.1038/sj.ijo.0803702
|View full text |Cite
|
Sign up to set email alerts
|

Zymosan-induced inflammation stimulates neo-adipogenesis

Abstract: Objective: To investigate the potential of inflammation to induce new adipose tissue formation in the in vivo environment. Methods and results: Using an established model of in vivo adipogenesis, a silicone chamber containing a Matrigel and fibroblast growth factor 2 (1 mg/ml) matrix was implanted into each groin of an adult male C57Bl6 mouse and vascularized with the inferior epigastric vessels. Sterile inflammation was induced in one of the two chambers by suspending Zymosan-A (ZA) (200-0.02 mg/ml) in the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 66 publications
3
34
0
Order By: Relevance
“…Interestingly, in this study, we saw that the chambers in the contralateral groin, containing Matrigel but not Zymosan, showed similar tissue growth, including vascularization and development, as the chambers containing Zymosan at all study endpoints (results not shown). This confirms that the response to Zymosan is most likely a systemic inflammatory response as demonstrated by the previous study by Thomas et al 10 and, therefore, influencing both chambers in the same animal. The contralateral chambers in this study could, therefore, not be considered a true control without Zymosan, and results are not shown.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Interestingly, in this study, we saw that the chambers in the contralateral groin, containing Matrigel but not Zymosan, showed similar tissue growth, including vascularization and development, as the chambers containing Zymosan at all study endpoints (results not shown). This confirms that the response to Zymosan is most likely a systemic inflammatory response as demonstrated by the previous study by Thomas et al 10 and, therefore, influencing both chambers in the same animal. The contralateral chambers in this study could, therefore, not be considered a true control without Zymosan, and results are not shown.…”
Section: Discussionsupporting
confidence: 77%
“…We recently demonstrated that adding Zymosan, a sterile inflammogen, to a Matrigel matrix in this closed model improves angiogenesis and adipogenesis, strongly suggesting that inflammatory cells/mediators are involved in these processes. 10 This study aims at characterizing the specific role that macrophages play in vascularized adipose tissue development. There are many arguments for a role of macrophages in blood vessel formation.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation and angiogenesis are closely interrelated, [55][56][57] and adipose angiogenesis is a key mediator in recruiting adipose precursor cells as well as the subsequent adipogenesis. 58,59 However, there was a reduced inflammatory level and larger final volume of adipose tissue in the PCL group compared with the control group in our study.…”
mentioning
confidence: 99%
“…Our hypothesis was introduced by Campiglio and Signorini: inflammatory background and chemokine network induced by the repairing process can cause the quiescent adipocytes or stem cells to proliferate excessively, finally forming the patient's PTL (6). There are many works that evaluated the association between adypogenesis and inflammation (15), in complex situations such as obesity or in laboratory experience with the use of highly flogogenic polysaccharides (16)(17)(18). This association was verified diminishing the concentrations of TNF alpha and IL6; the adipogenetic stimulation was dramatically suppressed (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%